2009
DOI: 10.1186/1471-2458-9-175
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's attitudes towards alcohol consumption

Abstract: Background: There is uncertainty as to whether there is a safe threshold for drinking alcohol during pregnancy. We explored pregnant women's attitudes towards drinking alcohol in pregnancy and their attitudes towards sources of information about drinking in pregnancy following recent changes in UK government guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
11

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 23 publications
6
92
0
11
Order By: Relevance
“…A 2010 survey of fellows of the ACOG found that two in five (40.1%) OB-Gyns believe that women can consume 1-2 drinks per week without risk of adverse pregnancy outcomes (Anderson et al, 2010). Combined with the subtleties of research on alcohol's effects during pregnancy, it seems likely that the competing opinions of health professionals and others can easily create confusion among laypersons (O'Leary et al, 2007;Raymond, Beer, Glazebrook, & Sayal, 2009). …”
Section: Competing Views On Alcohol Use During Pregnancy: Is Any Amoumentioning
confidence: 99%
“…A 2010 survey of fellows of the ACOG found that two in five (40.1%) OB-Gyns believe that women can consume 1-2 drinks per week without risk of adverse pregnancy outcomes (Anderson et al, 2010). Combined with the subtleties of research on alcohol's effects during pregnancy, it seems likely that the competing opinions of health professionals and others can easily create confusion among laypersons (O'Leary et al, 2007;Raymond, Beer, Glazebrook, & Sayal, 2009). …”
Section: Competing Views On Alcohol Use During Pregnancy: Is Any Amoumentioning
confidence: 99%
“…By profiling the context of the behaviour, and the knowledge, attitudes, beliefs, expectancies, and motivations of the target audience in terms of theoretical constructs, the effectiveness of message strategies can be strengthened. Although a number of qualitative and quantitative studies have provided insights into women's knowledge, beliefs, and attitudes with regards to alcohol use during pregnancy (Balachova, Bonner, Isurina, & Tsvetkova, 2007;Baxter, Hirokawa, Lowe, Nathan, & Pearce, 2004;Kesmodel & Kesmodel, 2002;Raymond, Beer, Glazebrook, & Sayal, 2009;Toutain, 2010), few describe formative research with the target audience that was used to develop message strategies aimed at preventing prenatal alcohol exposure (Branco & Kaskutas, 2001;Glik, Prelip, Myerson, & Eilers, 2008;Mengel, Ulione, Wedding, Jones, & Shurn, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Aun en países en los que existen planes de prevención de esta problemática, algunos estudios han señalado que las mujeres juzgan la información que se difunde en los medios masivos de comunicación como demasiado general, confusa e insuficiente, y creen que los profesionales de la salud deberían ser los encargados de brindar este tipo de información (7). En este sentido, la formación y actualización de los profesionales que trabajan en cuidados periconcepcionales y perinatales resulta fundamental.…”
Section: Consideraciones Finales: Algunas Estrategias De Prevenciónunclassified
“…Sin embargo, muchas mujeres no reciben asesoramiento o recomendaciones de los profesionales de la salud respecto del consumo de alcohol durante la gestación en los controles médicos preconcepcionales y prenatales. La mayoría de ellas carece de información respecto de las implicaciones del consumo de alcohol durante ese periodo o maneja información poco precisa transmitida por amigos, familiares o medios de comunicación (3)(4)(5)(6)(7).…”
Section: Introductionunclassified